Banking Crises and Financial Integration - Julian Caballero (Inter-American Development Bank (IDB), 2012)
This paper explores whether the level of financial integration of banks in a country increases the incidence of systemic banking crises. The paper uses a de facto proxy for financial integration based on network statistics of banks participating in the global market of interbank syndicated loans. Specifically, the network statistics degree and betweenness are used to proxy for the de facto integration of the average bank in a country. The paper fits a count data model in the cross-section for the period 1980- 2007 and finds that the level of integration of the average bank is a robust determinant of the incidence of banking crises. An increased level of de facto integration as mea- sured by borrowing by banks is positively associated with the incidence of crises. A higher level of de jure integration (capital account openness) is also associated with a higher incidence of crises. However, the results also indicate that prudential banking regulation (supervision) plays a crucial and much larger role in reducing the incidence of crises. Interestingly, the results also show that the level of integration as measured by betweenness of the average bank has a negative effect on the incidence of crises. That is, the more important the average bank of a country is to the global bank network, the fewer the number of crises the country endures.
Keywords: E44; E51; F21; F32; F34; G01; 330